Frankenstein or The Modern Prometheus And The Psychology of Mary Shelley - Çerkez, Sıla (Eastern Mediterranean University (EMU), 2013)
ABSTRACT: Humans are creatures many of whose worst fear is that they will disappear, who characterize themselves as unique creatures, who consciously want to increase their civilization, and who can imagine events that involve either part of their own experience or someone else’s experience; even events that have never really happened and creatures who have never really existed. Every human being has his/her own psychology and every person’s psychology differs due to individual experiences and beliefs. Human beings try to avoid feeling remorse by accommodating enormous defence mechanisms. Sometimes, they can accuse someone else or worse they can remain silent to try to lessen their remorse. Disappearing is the worst fear of human beings. Because of that fear, we develop survival instincts. We want to be recognized and accepted and some of us want to reproduce. To destroy the hunger of recognition, some want to reproduce to ensure their immortality or leave a work of art to penetrate human minds. Mary Shelley by writing Frankenstein or The Modern Prometheus, attempted to satisfy her hunger for recognition, gain approval and to satisfy her lack of self-confidence that lies behind the fear of not being accepted and stems from being repulsed by her father who raised her. She writes out of remorse in order to restore her mental health. In short, although there are lots of differences between Shelley’s psychology and that of her characters in Frankenstein or The Modern Prometheus my aim is mainly to show the similarities. Shelley’s main aim in writing such a novel may seem like creating a horror novel but by writing such a novel, she reflects her state of mind, and the novel becomes the fatalistic expression of her psychology. Keywords: Remorse, recognition, self-confidence. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: İnsanlar, birçoğunun en büyük korkusu yokolma olan, kendini üstün varlık diye tanımlayan, neslini bilinçli olarak çoğaltmak isteyen, ve gerek kendi, gerekse bir başkasının yaşamış olduğu olayları; hatta gerçekte hiç yaşanmamış olayları ve gerçekte hiç yaşamamış varlıkları hayal edebilen varlıklardır. Her insanın psikolojisi vardır ve her kişinin psikolojisi yaşanmışlıklar ve inançlardan ötürü birbirinden farklıdır. İnsanoğlu, muazzam savunma mekanizması üzenleyerek, vicdan azabından kurtulmaya çalışır. Bazen vicdan azabını azaltmak için bir başkasını suçlayabilir veya daha da kötüsü susabilir. Yokolma, insanoğlunun en büyük korkusudur. Bu korkudan dolayı, yaşamı sürdürme içgüdüleri geliştiririz. Tanınma, kabul görmek isteriz ve bazılarımız çoğalmak ister. Başkaları tarafından tanınma açlığını yoketmek için bazıları kendilerini güvenceye almak adına üremek ister veya insanların zihinlerine işleyen bir eser bırakmaya çalışır. Mary Shelley, Frankenstein ya da Modern Prometheus’u yazmakla hem tanınma açığını gidermeye, varlığını onaylatmaya, hem de babası tarafından büyütülürken kendisinde gelişmiş olan kabul edilmeme, reddedilme korkusunun altında yatan özgüven eksikliğini tatmin etmeye çalışmıştır. Shelley, akıl sağlığını düzeltmek adına vicdan muhasebesini dışavurmuştur. Kısacası, bu tezde Shelley'nin hayatı ve psikolojisi ile Frankenstein ya da Modern Prometheus’un karakterleri arasında birçok farklılıklar olsa da benim amacım benzerliklerini göstermektir. Shelley’nin bu eseri yazmasının esas nedeni bir korku hikayesi yazmak gibi görünse de bu eseri yazmakla, kendi akıl sağlığını yansıtmış ve bu eser psikolojisinin yazgısal dışavurumu olmuştur. Anahtar kelimeler: Vicdan azabı, tanınma, özgüven.
Master of Arts in English Language and Literature. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Arts, Humanities and Social Sciences, 2013. Supervisor: Prof. Dr. Nicholas Pagan.
Keywords: Arts, Humanities and Social Sciences; English Language and Literature; Shelley, Mary Wollstonecraft, 1797-1851 - Criticism and Interpretation; Shelley, Mary Wollstonecraft - Frankenstein or the Modern Prometheus - Frankenstein, Victor (Fictitious character) - Fiction; Remorse - Recognition - Self-Confidence